SEE+ computerized classroom-based training enhances 7- to 10-year-olds' socio-emotional cognition through observation and inference - Sveta Mayer; Iroise Dumontheil; Hannah R. Wilkinson; Kaska Porayska-Pomsta; Emily K. Farran; Andrew K. Tolmie; Denis Mareschal (PLoS ONE, 2025)
Smooth social interactions rely on children’s abilities to decode others’ social signals, which includes what an individual may say or do, and their facial emotional expressions. Failure can lead to exclusion from social groups. Consequently, a number of social and emotional learning (SEL) training programmes have been developed, with some evidence of positive impacts on those skills themselves and on academic achievement. Here, we present and evaluate the efficacy of a novel classroom-based computerized learning activity, called SEE+ (Socio-emotional engagement through observation), in supporting and enhancing 7- to 10-year-olds’ emotion recognition and theory of mind judgements through observation and inference. SEE+ involved observing four virtual characters interacting within social scenarios and inferring their mental states. Participants were recruited from across diverse school settings (rural, urban) in England as part of a large-scale randomised controlled trial (n = 5585; 7.3–11.0 years old, M age = 9.1, SD = 1.0) resulting in a mix of socio-economic and ethnic backgrounds. Mixed model ANOVAs were used to compare performance on socio-emotional tasks between the SEE+ group, an active control group and a teaching-as-usual control group. SEE + was associated with the equivalent of 4–6 months improvement in performance on the socio-emotional assessment tasks. Children showed near transfer effects of the intervention (i.e., when characters present in the computerized learning activity were used in the assessment), while no strong evidence of far transfer effects (i.e., when photographs of unknown children were used in the assessment) was found. Limitations were the use of pen-and-paper assessments with a reduced number of trials, and a possible ceiling effect in the older children in the photograph condition. Our findings point to the relative plasticity of younger children’s socio-emotional cognition and underscore SEE+ as an easy-to-use cost-effective socio-emotional resource for teachers to embed SEL in the school curriculum.